2008
DOI: 10.1177/000348940811701203
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic KTP Laser Photocoagulation Therapy for Pharyngolaryngeal Venous Malformations in Adults

Abstract: Photocoagulation using the KTP laser is a feasible and relatively safe treatment for pharyngolaryngeal venous malformations in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Laser therapy is a mainstay of management of mucosal and skin malformations. The Nd:YAG laser is the preferred laser at our institution, although the use of the KTP laser has also been described (Kishimoto et al , 2008). Patients with cervicofacial involvement will most often have an intraoral or airway component.…”
mentioning
confidence: 99%
“…Laser therapy is a mainstay of management of mucosal and skin malformations. The Nd:YAG laser is the preferred laser at our institution, although the use of the KTP laser has also been described (Kishimoto et al , 2008). Patients with cervicofacial involvement will most often have an intraoral or airway component.…”
mentioning
confidence: 99%
“…Kishimoto et al reported the cases of seven adults with pharyngolaryngeal VMs who were effectively treated using endoscopic potassium titanyl phosphate laser [5]. However, they also described that only surface photocoagulation could be achieved for bulky VMs.…”
Section: Discussionmentioning
confidence: 99%
“…Options for the treatment of adult laryngeal venous malformation include surgery with a skin incision and laser surgery . Surgery with a skin incision is highly invasive and often requires tracheotomy.…”
Section: Discussionmentioning
confidence: 99%